Gerakan Sosial dalam Perspektif Islam - Joharotul Jamilah (Refleksi: Jurnal Kajian Agama dan Filsafat, 2008)
This article captures the patterns and classification of religious-based social movements (read: Islam) in Indonesia that actively play a role in changing societal behavior. One interesting aspect to note is the growth and development of various typologies of Islamic social movements. These range from modernist Islamic movements to neo-modernist ones, and even to fundamentalist or radical movements.